Erythroblast island macrophages and their surface markers - Fang, Mei; Mei, Fengjun; Li, Guangrui (Frontiers in Hematology, 2025)
Erythroblast Island Macrophages (EIMs) are specialized cells that play a crucial role in erythropoiesis by forming erythroblastic islands (EBIs) and supporting the maturation of erythroblasts. These macrophages express a variety of surface markers that mediate their interactions with erythroblasts and regulate erythropoiesis. Most studies on EMIs rely on flow cytometry analysis and selecting the correct surface markers is of great importance when conducting research. This review provides a brief overview of the surface markers expressed by EIMs, including α5-integrin, CD11b, CD16, CD163, CD169, CD206, CSF1R, EPOR, F4/80, Gr1, MerTK, PPARγ, Timd4, and VCAM1. We also discuss the heterogeneity of EIMs and subsets of EIMs, such as F4/80+VCAM-1+CD169+EPOR+ macrophages.